IMPLEMENTATION OF THE ELSIMIL APPLICATION PROGRAM IN REDUCING THE INCIDENCE OF STUNTING IN SIDOARJO DISTRICT - Ihtifazhuddin, Fadhlillah; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyse the effectiveness of the ELSIMIL digital application in reducing stunting in Sidoarjo Regency through the lens of Edward III’s policy implementation theory. Method: A qualitative descriptive approach was employed with purposive sampling to select informants, while data were collected through interviews, observations, and documentation, and analysed using Miles and Huberman’s interactive model. Results: The findings reveal that effective communication, achieved through hierarchical information transmission, clarity of socialisation materials, and routine monitoring, supports programme success despite challenges such as limited TPK understanding and server disruptions. Resource-related obstacles include limited cadres, uneven authority comprehension, and suboptimal technological infrastructure; however, strong commitment and enthusiasm among implementers facilitated programme sustainability. A well-structured bureaucratic framework with clear Standard Operating Procedures and division of tasks enabled the creation of a stunting prevention ecosystem integrating digital technology with community-based health services. Novelty: This study contributes an innovative model for addressing the digital divide in public health interventions by adapting communication and training strategies to the technological literacy of grassroots health cadres, thereby strengthening bottom-up approaches to stunting prevention.